Cutibacterium Acnes induces Alzheimer’s disease-like pathology in brains of wistar rats through structural changes associated with microtubules - Morteza Aliashrafi; Mohammad Nasehi; Seyed Davar Siadat; Mohammad-Hossein Mohammadi-Mahdiabadi-Hasani; Hakimeh Zali; Zahra Niknam (Behavioral and Brain Functions)
Abstract Background Cutibacterium acnes ( C. acnes), a Gram-positive anaerobe and a dominant bacterium species in the sebaceous follicles of the face was detected in the brain of Alzheimer’s disease (AD) patients. It has been found that C. acnes activates non-specifically the innate immune system by producing proinflammatory cytokines and can participate in brain inflammation. We hypothesise that C. acnes could influence the brain through the structural alteration in axons and dendrites of neurons. Methods In this regard, the hippocampus of rats was infected with C. acnes, and memory retention, amyloid-β (Aβ1–42) deposition, hyperphosphorylated tau protein (p-Tau) formation, and expression levels of MAP2 and β-tubulin proteins in the hippocampus tissues were investigated. Results C. acnes-infected rats displayed memory deficits and Aβ1–42 deposits were detected in their hippocampus tissue up to 7 days post-infection. C. acnes was neurotoxic and exerted detrimental effects on MAP2 and β-tubulin proteins, which are required for normal neuronal function. An elevated level of p-Tau was also identified in infected animals. Conclusion Based on these results, we propose that C. acnes infection of the brain participates in the initiation of the pathogenesis of sporadic AD through degeneration of axons and dendrites. Graphical Abstract